Effect of Ruminally-Protected Lysine Supplementation to Growing Cattle on Growth and Subsequent Finishing Performance - K. J. Hazlewood; M. S. Grant; D. A. Blasi; G. A. Ducharme; E. C. Titgemeyer (Kansas Agricultural Experiment Station Research Reports, 2022)
Objective:The objective of this study was to evaluate the effects of ruminally-protected lysine supplementation fed during the growing phase to cattle limit-fed a corn-based diet, and to evaluate the subsequent finishing performance. Study Description:For 77 days, a group of 338 steers limit-fed at 2.4% of body weight daily on a dry matter basis were allocated to treatments providing 0, 3, or 6 g/day of lysine from Smartamine ML (Adisseo, Alpharetta, GA), or containing blood meal plus ruminally-protected methionine from Smartamine M. Growth performance was measured over the growing period. Cattle were then shipped to a commercial feedlot and fed without treatment until slaughter. Finishing performance was gathered from carcass data. Results:Steers supplemented with 3 g/day of lysine appeared to have the greatest response during the growing phase, having the heaviest body weights on day 77, and greatest average daily gains and gain:feed ratios. In the finishing phase, cattle that received 3 g/day of lysine during the growing phase maintained the weight advantage, relative to the control, established during the growing phase. Cattle receiving 6 g/day of lysine during the growing phase performed best during the finishing phase. Cattle receiving 3 and 6 g/day of lysine during the growing phase had carcasses that were 8 and 16 lb greater, respectively, than the control. The Bottom Line:When fed corn-based diets, supplementation of ruminally-protected lysine during the growing phase may improve growth performance of cattle during the growing and/or finishing phase, leading to improvement in greater carcass weights.
Keywords: lysine; growing cattle; corn-based